Interinstitutional Interaction between the Head of State and the US Congress: Historical Context and Modern Features - E. S. Shevchenko (Управленческое консультирование)
The specific of political and political-administrative management of the United States reveals some problematic aspects of realization of official competencies by the head of state from the perspective of positive political relations with American congressmen related to achieve political consensus and make agreed political decisions. In this regard, the search for effective political mechanisms and tools of interinstitutional interaction of executive and legislative authorities at the present stage of the US political development is actualized. Normative and legal bases of political and administrative functions of the US President and the US Congress are considered. Political and historical features of interinstitutional interaction of executive and legislative authorities in the United States are analyzed. The key factors and conditions of conflictogenicity of political relations with American congressmen in the framework of D. Trump’s presidency are identified. The main reasons and circumstances of deepening interinstitutional contradictions in the US political system with regard to J. Biden’s functional role are formulated. It is concluded that it is necessary to build political trust and use approbated political tools approved by the US President and American legislators. At the same time, real causes of political events observed in the United States have an objective nature and need a more in-depth and detailed analysis. As a result, problematic planes and levels of political-administrative relations between the state bodies of executive and legislative power in the United States at the present stage are presented. The author used quantitative (multifactorial analysis, statistical presentation of data) and qualitative (content analysis, secondary analysis of data from American analytical and scientific research centers) methods.